The Antioxidant and Anticoagulant Effects of Coumarin and Quercetin from Cinnamon Methanolic Extract, and the Assessment of Cinnamon Powder Effect on Plasma Parameters in Diabetes, and the Disinfectant Activity in Diabetic Patients - Elmira Ahmadi; Mahnaz Mahdavi Shahri * (Lorestan University of Medical Sciences, 2020)
Background and Aim: This research tries to study the impact of cinnamon nutritional supplement on the blood glucose and lipid monitoring indicators in patients diagnosed with type II diabetes. The first aim of the present study was to evaluate the in vitro antioxidant and anticoagulant effects of flavones and coumarin from cinnamon methanolic extract (Cin@m-Ext). The second aim of this research was to study the impact of cinnamon powder capsule (Cin@p-Cap) on the beta cells of the pancreas in patients with type II diabetes. Materials and Methods: This clinical trial was carried out on 160 patients diagnosed with type II diabetes. The 4 groups took edible capsules containing cinnamon (500 mg, 4 times daily). At the end of the intervention, a remarkable reduction in the fasting blood glucose was observed in the group receiving cinnamon comparing to the group taking a placebo. Results: The results indicated a significant decrease of the blood clotting time in the presence of Cin@m-Ext in comparison with the control. A high-performance liquid chromatography (HPLC) procedure has been described to determine natural compounds in cinnamon methanolic extracts. Hence, it was concluded that the presence of high quercetin, ellagic acid and coumarin was influential in prolonging blood clotting in the intrinsic pathway. The antioxidant activity also indicated that Cin@m-Ext could be used as a potential radical scavenger, and also indicated that DPPH activity could increase in a dose-dependent manner. Conclusion: These results indicated that the consumption of Cin@p-Cap might be useful in controlling and reducing the blood glucose levels by improving insulin sensitivity or reducing the rate of the absorption of carbohydrates in the small intestine among type II diabetic individuals.